Teori sastra Marxis dan aplikasinya pada penelitian karya sastra Arab modern - Manshur, Fadlil Munawwar (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Many works of modern Arabic literature contain themes of class struggle, especially the struggle of the oppressed against the oppressors. Indeed, the theme of class struggle in Arabic literary works serves as a moral and social mirror of Arab society itself. By reviewing modern Arabic literary works from the perspective of Marxist literary theory, these works can be understood as representations of intense social class conflict within Arab society. Therefore, the use of this theory can help reveal more meaningful and authentic interpretations of Arabic literature and avoid the marginalization of Arab literary works in the construction of cultural and ideological discourse.